KARAKTERISTIK PENGERINGAN DAN MUTU HEDONIK GULA KELAPA KRISTAL MENGGUNAKAN PENGERING TIPE RAK BERPUTAR BERENERGI LIMBAH TERMAL DAN BIOMASSA - Syska, Kavadya; Ropiudin, Ropiudin (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Drying is one of the critical points in the process of making crystal coconut sugar. The production of crystalline coconut sugar in Banyumas Regency is very potential to be developed, but the drying of crystalline coconut sugar that has been carried out in Banyumas Regency still uses natural drying. The dryer used in this study is a rotating rack type dryer. This study aims to 1) examine changes in the water content of crystal coconut sugar in a rotating rack type dryer, 2) examine changes in the drying rate of crystal coconut sugar in a rotating rack type dryer, and 3) examine the physical and chemical properties of crystal coconut sugar dried using a rotary dryer. rotating rack. The research was conducted at the Integrated Science Laboratory, Nahdlatul Ulama University, Purwokerto. The research was carried out from February to July 2022. The experimental design that was carried out was a Completely Randomized Factorial Design with the influence of temperature and drying time. The research was conducted to find out the best drying time and temperature as well as to observe the moisture content, sucrose content, pH, and organoleptic tests which included color, taste, and texture. The results showed that changes in drying rate had a very significant effect on water content, sucrose content, pH, and organoleptic tests on color and texture, but drying rates had no significant effect on organoleptic tests on taste. The best temperature and time in the drying process using a rotating rack type dryer is the G3K2 treatment, drying using a temperature of 80 oC for 2 hours.